2018
DOI: 10.1038/s41419-018-0969-z
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CCAL/miR-149/FOXM1 axis promotes metastasis in gastric cancer

Abstract: Early evidence indicates that the long non-coding RNA CCAL plays a critical role in cancer progression and metastasis. However, the overall biological role and clinical significance of CCAL in gastric tumourigenesis and progression remain largely unknown. We observed that CCAL was upregulated in gastric cancer tissues and was associated with the tumour-node-metastasis stage. Functional experiments showed that CCAL promoted gastric cancer cell proliferation and metastasis in vitro and in vivo. Luciferase report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Although the early diagnosis and therapy of GC were rapidly developed over the past decades, most of the patients with GC were faced with metastasis recurrence [31][32][33]. It is important for GC patients to search out effective new biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the early diagnosis and therapy of GC were rapidly developed over the past decades, most of the patients with GC were faced with metastasis recurrence [31][32][33]. It is important for GC patients to search out effective new biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the luciferase activity had no significant change when the corresponding target sites were mutated in MKN-28 and MGC-803 cells (Figures 4 C, D). In addition, we found that miR-149 was down-regulated in human GC tissues compared with that in the corresponding non-cancerous tissues (Figure 4 MiR-149 exerted an anti-oncogenic effect in vitro by targeting IL-6/STAT3 signaling miR-149 as an anti-oncomiR has been reported during GC tumorigenesis [19]. Interestingly, IL-6 is a direct target involved in miR-149-associated oncotherapy [24,29].…”
Section: Low Expressionmentioning
confidence: 82%
“…We also found that the expression of miR-149 was significantly and negatively correlated with hsa_circ_0017728 in GC tissues, suggesting that miR-149 exerted a negative function with hsa_circ_0017728 in the progression of GC. Previous studies have reported the miR-149 primarily serves as an anti-tumor miRNA, and its expression levels are repressed in multiple types of cancers, including HCC [34], breast cancer [35] and GC [19]. Luo et al showed that over-expression of miR-149 suppresses HCC cell migration and invasion in vitro [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations